(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This research looks at how different wellness metrics might affect productivity in the workplace.More and more businesses are spending money on wellness programs for their employees in an effort toboost health and reduce medical expenses. Unfortunately, the effectiveness of such initiatives is not wellstudied.In addition, sophisticated statistical methods, such as the standard deviation and other variabilitymeasurements, and regression analysis to determine correlations among variables, were taken intoaccount. The research concluded that wellness initiatives have an effect on the efficiency of businesses.This was accomplished via preventative care, education and training on the significance of wellness onworkers, and a management who was supportive of these initiatives.